Improving Islamic Religious Education Teachers' Performance Through Effective School Leadership - Zaini, Abdul Wahid; Sanjani, M Aqil Fahmi (Universitas Nurul Jadid, 2023)
This study focuses on the role of school leadership in enhancing the performance of Islamic Religious Education (PAI) teachers at Madrasah Tsanawiyah. The primary objective of this research is to examine how effective leadership practices by the school principal can influence the professional development and teaching quality of PAI teachers. A qualitative approach with a case study method was employed to gain an in-depth understanding of the dynamics within the school environment. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that consistent and supportive leadership significantly contributes to the improvement of teacher performance, particularly through professional development, classroom observation, and performance evaluation. The study underscores the importance of structured leadership strategies in fostering an educational environment conducive to both teacher growth and student success. The implications suggest that school leaders should adopt more systematic and frequent evaluation practices to sustain and enhance teacher performance.